Catalytic oxidation of cinnamyl alcohol to cinnamaldehyde using hydrogen peroxide - Nyamunda, Benias C.; Moyo, Mambo; Chigondo, Fidelis (2016)
Platinum-bismuth bimetallic catalysts supported on activated carbon powder were prepared using a colloidal method. The catalysts and their support were characterized by physisorption, Brunauer Emmet Teller (BET), high resolution transmission electron microscopy (HRTEM), scanning electron microscopy (SEM) and X-ray diffraction (XRD). The selectivity and activity of the catalysts were tested for the oxidation of cinnamyl alcohol using H2O2 as an oxidant. The effects of concentration, solution medium and modifier on catalysts selectivity and activity were investigated. The results showed that hydrogen peroxide could be used as an effective oxidant for the catalytic oxidation of cinnamyl alcohol. Selectivity of cinnamaldehyde (84%) was attained at 34% conversion of the cinnamyl alcohol. The catalysts were more active in water than in toluene.